2022
DOI: 10.3389/fpsyt.2022.794652
|View full text |Cite
|
Sign up to set email alerts
|

Neural Effects of Physical Activity and Movement Interventions in Individuals With Developmental Disabilities–A Systematic Review

Abstract: Individuals with developmental disabilities present with perceptuo-motor, social communication, and cognitive impairments that often relate to underlying atypical brain structure and functioning. Physical activity/movement interventions improve behavioral performance of individuals with and without developmental disabilities. Majority of the evidence on potential neural mechanisms explaining the impact of physical activity/movement interventions is based on studies in individuals with typical development; ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 145 publications
(305 reference statements)
0
9
0
Order By: Relevance
“…A significant instance of pervasive development being witnessed throughout the globe is the complex neurodevelopment condition called autism spectrum disorder (ASD) which impacts behavior, communication, and social interaction (1)(2)(3)(4). The scientific community has conducted several research studies in recent years to assess the incidence and prevalence of ASD (5)(6)(7). A significant increase in ASD could be globally recognized (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…A significant instance of pervasive development being witnessed throughout the globe is the complex neurodevelopment condition called autism spectrum disorder (ASD) which impacts behavior, communication, and social interaction (1)(2)(3)(4). The scientific community has conducted several research studies in recent years to assess the incidence and prevalence of ASD (5)(6)(7). A significant increase in ASD could be globally recognized (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…DCD can occur alone or with other diseases and disorders. In particular, it can coexist with ADHD ( Su et al, 2022 ). In addition, studies have confirmed that children with DCD exhibit sensorimotor disorders, balance and postural control disorders ( Fong et al, 2013 ), motor planning deficits ( Hyde and Wilson, 2013 ), and visuospatial deficits ( Alloway, 2011 ), which are important factors in the occurrence of DCD.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we expect that the AON network will be active during MI, ME, and MO, but primary motor regions will show greater activity during ME. This study aims to elucidate the differences between ME, MO, and MI during an ecologically valid EEG-fNIRS paradigm, better characterizing “target neural mechanisms” that may benefit future therapies or interventions 30 .…”
Section: Introductionmentioning
confidence: 99%